Epitaphios logos – hybrydyczny gatunek retoryki ateńskiej - Tuszyńska , Krystyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
Athenian funeral oration (epitaphios logos) belongs to the epideictic rhetoric. But according to Aristotle the topics used in epideictic oratory could be applied in the deliberative kind, after some modification in the matters of language. In this article I consider the means proposed in the narrative part of the composition, which can be used instead of argumentation in epideictic oratory, i.e. amplification, metaphors and actualization (putting things before the eyes, gr. energeia, lat. evidentia). My purpose is to answer the question who was/is the recipient of Athenian funeral oration. In my opinion there are three kinds of primary recipients: the dead soldiers in the battle, the listeners present at the celebration (Athenians and foreigners) and the Idea of Democracy itself. I also try to find the so-called secondary recipient of Athenian funeral oration. I treat Athenian funeral oration as a hybrid genre of Greek rhetoric.